Factors Affecting Nursing Students’ Learning - Ariadni, Dwi Karina; Ariga, Reni Asmara (Talenta Publisher, 2020)
High learning motivation is influenced by some factors from intrinsic factor (in self) and extrinsic factor. This study aims to describe the intrinsic factors and extrinsic factors in learning motivation. This is a descriptive design study with quota random sampling. 90 respondents were involved in this study. Results of intrinsic factors measured by interest in the field of knowledge studied: 47.8% of respondents collect tasks given in accordance with the time set, and 41.1% of respondents diligently follow the lecture. The results of the study of extrinsic factors are measured by the quality of lecturers who teach: 51.1% of lecturers often provide questions clearly and briefly. Based on the method of lecturing: simulation methods in the laboratory often increase the motivation to learn. Based on the lecture’s room: 57.8% stated that a clean lecture’s room can improve the concentration of learning. Based on the complete book in the library: 47.8% encourage respondents to do the task quickly. Based on the learning facilities: 47.8% are always motivated to learn if the lecturer uses LCD. Support of parents (76.7%) in meeting the needs of respondents in learning.The management of nursing education is suggested to motivate students during lectures based on intrinsic factors and extrinsic factors. Keywords : learning motivation, affecting factor, nursing student